1990
DOI: 10.1002/ijc.2910460513
|View full text |Cite
|
Sign up to set email alerts
|

Survival of breast‐cancer patients and body size indicators

Abstract: The association of breast-cancer survival with various risk factors was investigated using data of 213 breast-cancer patients who underwent surgical operation between 1975 and 1978. They were followed-up until 1987, and a total of 64 deaths including 47 breast-cancer deaths were certified. The 5-year and 10-year relative survival rates were 78.5% and 75.3% respectively. Of the various factors investigated, some anthropometric indicators revealed interesting results; i.e., body weight, Quetelet index, and body … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
26
0

Year Published

1994
1994
2008
2008

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(34 citation statements)
references
References 19 publications
8
26
0
Order By: Relevance
“…Others have also reported that leptin can augment matrix metalloproteinase production in trophoblasts and endothelial cells (50 -52), although this has not been reported in cancer cells. In addition, an epidemiological study has also indicated that breast cancer in obese women is more aggressive, with a poor prognosis (53). These facts, together with our results, support the possibility that the leptin-OB-R signal can play positive roles in breast cancer metastasis.…”
Section: Fig 1 Immunohistochemical Staining Of Leptin (A-c) and Ob-rsupporting
confidence: 88%
“…Others have also reported that leptin can augment matrix metalloproteinase production in trophoblasts and endothelial cells (50 -52), although this has not been reported in cancer cells. In addition, an epidemiological study has also indicated that breast cancer in obese women is more aggressive, with a poor prognosis (53). These facts, together with our results, support the possibility that the leptin-OB-R signal can play positive roles in breast cancer metastasis.…”
Section: Fig 1 Immunohistochemical Staining Of Leptin (A-c) and Ob-rsupporting
confidence: 88%
“…As the BMI selected threshold values were 24 and 25 kg/m 2 , the role of excess weight in breast cancer prognosis starts to become significant at the WHO-defined threshold (cutpoint) for overweight. The W, IWR and BSA cut-offs are [18] found that there was a 12% difference in survival likelihood between patients with a BMI of 20 kg/m 2 and those with a BMI of 24 kg/m 2 , after a 10-year of follow-up. Kimura et al [1] defined stout patients as those with a BMI of at least 23 kg/m 2 , and revealed a significantly lower survival probability for stout post-menopausal women after a 10-year follow-up, when compared to leaner patients with a BMI lower than 21 kg/m 2 .…”
Section: Discussionmentioning
confidence: 99%
“…The Disease Free Interval (DFI), including the absence of metastases, nodal or local recurrences, was also explored. We thus computed several BSI from the patients' weight and height: BMI expressed in kg/m 2 , W in kg, IWR [18,25]. The search for optimal binary BSI cut-offs was supported by an observed continuous monotonous relationship between BSI and prognosis events in the studied population (data not shown).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations